Poly(ADP-ribose) polymerase inhibition in pancreatic cancer - Singh, Hans Martin; Bailey, Peter; Hübschmann, Daniel; Berger, Anne Katrin; Neoptolemos, John P.; Jäger, Dirk; Siveke, Jens; Springfeld, Christoph (Genes, chromosomes & cancer, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease with limited treatment options. Recently, the poly(ADP-ribose) polymerase inhibitor (PARPi) olaparib has been approved for maintenance therapy after successful platinum-based chemotherapy in patients with germline mutations in BRCA1 and BRCA2. Approval was based on the POLO study that has shown a significant improvement in progression-free survival for patients with metastatic PDAC after at least 4 months of platinum-based chemotherapy. Hopefully, this first biomarker-directed targeted therapy for a relevant subgroup of pancreatic cancer patients is only the beginning of an era of personalized therapy for pancreatic cancer. The potential role for PARPi in improving survival in patients with pancreatic cancer containing somatic tumor mutations has yet to be established. Multiple studies investigating whether PARPi therapy might benefit a larger group of pancreatic cancer patients with homologous recombination repair deficiency and whether combinations with chemotherapy, immunotherapy, or small molecules can improve efficacy are currently underway. We here review the molecular basis for PARPi therapy in PDAC patients and recent developments in clinical studies.